The Nanomaterial role in the re-classification costs of modern manufacturing product - Wissam Aziz Shnawa (Journal of Madenat Alelem University College, 2017)
The Nanomaterial of the most important modern concepts when economic units entered in production, it will present the characteristics of products and features that exceed those that are produced in traditional ways, In view of the progress of scientific and technological development, which has led to increased intensity of competition on the economic units should be oriented towards the application of the concepts that will help the introduction of Nanomaterial in production and reap the benefits accruing from it, find has acquired importance by identifying the impact of Nanomaterial on the structure of modern industrial product costs, as research aims to review the impact of Nanomaterial on the cost accounting, The research found that the modern manufacturing product costs shifted from direct materials , direct labor and indirect manufacturing costs to only indirect manufacturing costs.